Watershed complexity increases the capacity for salmon–wildlife interactions in coastal ecosystems. Issue 2 (20th November 2019) - Armstrong, Jonathan B.; Schindler, Daniel E.; Cunningham, Curry J.; Deacy, William; Walsh, Patrick
Abstract: Habitat alteration and species exploitation are fundamental issues in conservation, yet their interacting effects on food webs are rarely considered. We used a foraging model based on the Wood River basin (Alaska, USA) to explore how watershed development and commercial fisheries affect energy flow from sockeye salmon to brown bears. We found that, where salmon are abundant, fisheries can harvest large fractions of runs without substantially reducing bear consumption of salmon, but that watershed development could strongly reduce bear consumption if it shortens the duration of foraging opportunities by reducing population‐level variation in salmon spawn timing. Habitats with the lowest resource abundance (small streams) were particularly profitable for bear foraging because they offer salmon at unique times of the season. This result challenges environmental impact assessments that assume ecological effects respond solely to changes in resource abundance.